Serious underestimation of reduced carbon uptake due to vegetation compound droughts - Jiaxi Song; Sha Zhou; Bofu Yu; Yan Li; Yanxu Liu; Ying Yao; Shuai Wang; Bojie Fu (npj Climate and Atmospheric Science, 2024)
Abstract Compound droughts with low soil moisture (SM) and high vapor pressure deficit (VPD) pose significant threats to terrestrial carbon sink and agricultural production. However, the frequency and intensity of compound droughts and their adverse impacts on the carbon cycle remain highly uncertain. Here, we define and identify vegetation compound droughts (VCDs) when low SM and high VPD severely limit and adversely affect vegetation carbon uptake. We find frequent and severe VCDs and their considerable adverse impacts on carbon uptake in mid- and low-latitude regions, particularly in drylands. Risks of VCDs have been greatly underestimated as the widely adopted quantile-based approach identifies only 11% of VCDs and 26% of global GPP anomalies due to VCDs. The frequency and intensity of VCDs and their adverse impacts on carbon uptake are projected to increase further, irrespective of whether the CO2 fertilization effect on vegetation growth and photosynthesis is considered or not. These findings improve our understanding of current and future risks of VCDs and underline the importance of adaptation measures to cope with the adverse impacts of ever-increasing compound droughts.